The effects of season (spring versus autumn) on diagnosis of normocalcemic primary hyperparathyroidism - Basińska-Lewandowska, Magdalena; Lewiński, Andrzej; Lewandowski, Krzysztof C.; Skowrońska-Jóźwiak, Elżbieta (Frontiers in Endocrinology, 2022)
Background Raised parathormone (PTH) and normal calcium concentrations can be observed both in normocalcemic primary hyperparathyroidism (nPHPT) and in secondary hyperparathyroidism, e.g. due to vitamin D deficiency. We assessed the impact of season on the validity of diagnosis of nPHPT in terms of screening investigations to be performed in the primary care settings. Material and methods On two occasions (March/April & September/October) we measured vitamin D (25OHD), PTH and total calcium in 125 healthy subjects, age range 6-50, not taking any vitamin D supplements. Results In autumn there was an increase in 25OHD concentrations (from 18.1 ± 7.37ng/ml to 24.58 ± 7.72ng/ml, p<0.0001), a decline in PTH from 44.40 ± 17.76pg/ml to 36.63 ± 14.84pg/ml, p<0.001), without change in calcium levels. Only 45 subjects (36%) were vitamin D sufficient (25OHD>20/ml) in spring versus 83 (66.4%) in autumn, p<0.001. Elevated PTH concentrations were noted in 10 subjects in spring (8%) and in six subjects (4.8%) (p<0.05) in autumn. In spring, however, eight out of ten of these subjects (80%) had 25OHD<20 ng/ml, versus one in six (16.7%) in autumn (p<0.01). Normalization of PTH was observed in seven out ten subjects (70%), and all of them had 25-OHD<20 ng/ml in spring. Conclusions In spring elevated PTH concentrations in the setting of normocalcemia are more likely to be caused by 25OHD deficiency rather by nPHPT. In contrast, in autumn, increased PTH concentrations are more likely to reflect nPHPT. We postulate that screening for nPHPT should be done in 25OHD replete subjects, i.e. in autumn rather than in spring.